Developing and Validating a Test of Higher Order Thinking Skills for Future Teachers - Maimoona Naeem; Rizwan Akram Rana (JCTE, 2025)
Higher-order thinking skills (HOTS) are extremely needed to be possessed by future teachers but there is less work on the development of suitable measuring instruments for HOTS (Zhou et al., 2023). The present study is intended to develop an instrument to test the higher order thinking skills (HOTS) of future teachers at university level. The instrument named as Maimoona Higher Order Thinking Skills Test (MHOT). The developed test is delimited to two main HOTS: Creative and Critical thinking skills. These HOTS are distinct as well as have inter-dependency. There are total fourteen interpretive exercises/items in the instrument. To meet the psychometric criteria the construct validity evidence (n = 200) was gathered through exploratory factor analysis (EFA). The convergent validity evidence was also collected and established by using the College Assessment Academic Proficiency of Critical Thinking (CAAP) test with the average variance 0.65 and composite reliability of 0.92 between MHOT and CAAP. The inter-rater reliability value of Kappa was 0.724 and the Cronbach’s alpha value of the entire instrument was 0.91. The content validation process involved four experts in total, three content experts from the discipline of Education and one from the discipline of Psychology. Scale content validity index (SCVI) was 0.93. Item analysis was also conducted to ensure the discrimination index of the items and all items were falling under the acceptable criteria except two items.